Towards an integrated evaluation approach for cultural urban landscape conservation/regeneration - Francesca Nocca; Luigi Fusco Girard (REGION, 2018)
The contemporary economic crisis (and also ecological and social crisis) calls for a new model of urban development. The international debate is today focused on the necessity of a new paradigm (Hosagrahar et al., 2016) that will define sustainable development policies and programmes: this new paradigm moves the concept of development towards a more humanistic and ecological point of view. The recent international debate around Sustainable Development Goals (SDGs) is going to highlight the role of cultural heritage for sustainable development (United Nations 2016, 2015a). Cultural heritage can play a critical role in the achievement of the above mentioned new humanistic and ecological paradigm of sustainable cities. In this paper some indicators to evaluate cultural urban landscape conservation/regeneration projects are identified, starting from case studies. The purpose of the analysis of good practices is to support the elaboration of a multidimensional matrix that can produce empirical evidence about the impacts of cultural urban landscape conservation/regeneration. After a particular focus on the relationship between variation of landscape and variation of wellbeing, this paper will present a methodological proposal to evaluate cultural urban landscape conservation/regeneration projects.
Keywords: 330; Cultural Heritage conservation; landscape variation/wellbeing variation; multidimensional indicators